Emotions and the organizational fabric - Ashkanasy, Neal M. 1945-; Härtel, Charmine E. J. 1959-; Zerbe, W. J. (Emerald, 2014)
Emotion in an organization is much more than a phenomenon experienced solely by its members it is a deeply embedded component of the organizational fabric. Consistent with this idea, chapters in this volume deal with emotion at all levels of organizing: at the individual level, expressed in interpersonal exchanges and in groups, and across the organization as a whole. They represent a selection of papers from the Eighth International Conference on Emotion in Organizations, held in July 2012 in Helsinki, Finland; plus a selection of invited chapters. Chapters thus represent cutting-edge articles by leading and emerging scholars of emotion in organizations from around the world. Specific topics include creation of positively deviant business-to-business services, leader effectiveness and emotions in crisis situations, gender and role conflict among managers, developing shared wellbeing in communal settings, the nature of emotional labor across levels, managing workplace aggression, building customer passion, developing mindfulness, emergence of expectations, emotionalizing institutional theory, bullying as a form of institutional control, and how employees project competence.